Managers and management in Vietnam : 25 years of economic renovation (doi moi) - Edwards, Vincent, 1947- (Routledge studies in the growth economies of Asia (2005) ;, 2013)
"This book presents a comprehensive overview of managers and management in Vietnam, based on extensive original research, including interviews with a large number of managers in Vietnam. It shows how management in Vietnam is best understood from the perspective of Vietnamese managers themselves, rather than in terms of Western or Asian models of management."--Publisher's description.